Implementation of the Merdeka Curriculum in English Learning at MA Al Amiriyyah in the Academic Year 2023/2024 - Ahmada, Adib; Fauziana, Dwi Agustin (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2025)
This study explores the implementation of the Merdeka Curriculum in English learning at MA Al Amiriyyah, focusing on classes X and XI. The objective is to assess the effectiveness of different learning models applied by the English teachers. A qualitative approach was employed, collecting data through interviews, observations, and documentation. The results indicate that the problem-based learning model in class XI was less effective due to its mismatch with student conditions, leading to disengagement and boredom among students. Conversely, the project-based learning and cooperative learning models in class X were highly effective, fostering an active, creative, and responsible learning environment. These models allowed students to engage more deeply with the material and take greater ownership of their learning process. These findings highlight the critical need for selecting and implementing appropriate learning models to maximize student engagement, motivation, and overall learning outcomes in line with the objectives of the Merdeka Curriculum